EVALUASI PENGGUNAAN E-PUSKESMAS MENGGUNAKAN METODE HUMAN, ORGANIZATION, TECHNOLOGY DAN NET-BENEFIT DI PUSKESMAS LUBUK BUAYA PADANG - Dian Sari; Maisharoh Maisharoh (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
E-Puskesmas is a health service application that is used in all services, especially in the registration and reporting section at the Puskesmas. The use of e-Puskesmas at the Lubuk Buaya Padang Health Center still has problems that interfere with registration and reporting. The purpose of this study was to determine the evaluation of the use of e-Puskesmas using the HOT-Fit method at the Lubuk Buaya Health Center. This type of research is qualitative using a phenomenological approach. This research was conducted at the Lubuk Buaya Padang Health Center from May to June 2022 with four informants conducted by means of interviews and observations. Data is processed by triangulation method and analyzed using collaizi. The results obtained from the human, the obstacles are the implementation of training, network problems, reporting that is still manually. Aspect organizational has obstacles, including the organizational structure has not been updated and the SOP on e-Puskesmas has not been socialized. Aspect technology is the problem with the system error in the e-Puskesmas application so that it interferes with the patient registration process. Based on the results of research, the use of e-Puskesmas seen from several aspects of registration and reporting is still not optimal, therefore in the use of e-Puskesmas it is necessary to pay attention and overcome the things that become obstacles in its use such as networks, socialization of e-Puskesmas SOP and applications e-Puskesmas need to be improved to minimize service process problems.